Inequality in children's well-being and development: Evidence from a national panel study. (March 2015) - Xu, Hongwei; Liu, Airan; Zhang, Yueyun
China's rapid socio-economic and demographic changes have raised concerns about growing socio-economic inequalities in children's well-being. Drawing on the data from the 2010 and 2012 waves of the China Family Panel Studies (CFPS), this study systematically examines the socio-economic inequalities in children's objective and subjective well-being as well as differentials in children's growth trajectories. We find strong evidence of persistent urban advantage in an array of child development indicators, despite the overall economic boom since the beginning of the reform era. However, we also find that children from families of low socio-economic status (SES) attained certain non-cognitive advantages relative to those from better-off families, which may help offset certain negative impacts of low SES. Furthermore, the experience of rural-to-urban migration appears to be beneficial to rural-origin children as their exposure to a novel urban environment likely raises their educational aspiration, among other measures, which in turn is related to increased educational investment.